2011
DOI: 10.1088/0957-4484/22/33/335701
|View full text |Cite
|
Sign up to set email alerts
|

Transport behavior and negative magnetoresistance in chemically reduced graphene oxide nanofilms

Abstract: The electron transport behavior in chemically reduced graphene oxide (rGO) sheets with different thicknesses of 2, 3, and 5 nm was investigated. The four-probe method for the sheet resistance (R(S)) measurement on the intensively reduced graphene oxide samples indicates an Arrhenius characteristic of the electron transport at zero magnetic field B = 0, consistent with previous experimental results on well-reduced GO samples. The anticipated variable range hopping (VRH) transport of electrons in a two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In this work, we report the results of magnetoresistance (MR) measurements in samples of monolayer graphene strongly disordered with ion irradiation. MR in the VRH regime of conductivity has been observed earlier in different graphene-based structures: fluorinated graphene [4], graphene exposed to ozone [5], graphene oxide [6]. In Ref.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this work, we report the results of magnetoresistance (MR) measurements in samples of monolayer graphene strongly disordered with ion irradiation. MR in the VRH regime of conductivity has been observed earlier in different graphene-based structures: fluorinated graphene [4], graphene exposed to ozone [5], graphene oxide [6]. In Ref.…”
Section: Introductionmentioning
confidence: 53%
“…Defects are very useful tool to modify and control the physical properties of true two-dimensional (2d) material -monolayer graphene, therefore, disordered graphene attracts a lot of attention [1,2,3,4,5,6,7]. The evolution of optical (Raman spectra) and electronic (conductivity) properties of graphene with increasing disorder has been investigated in many papers (see, for example, [8,9,10,11]).…”
Section: Introductionmentioning
confidence: 99%
“…Although other studies have reported a variation from VRH to activated transport 12 or space charge limited conduction 13, these mechanisms are still dominated by the effects of disorder. A recent study has shown activated transport in RGO indicating band‐like transport 14.…”
Section: Introductionmentioning
confidence: 97%
“…Plots of ln( I / V ) vs 1/ T is shown in Figure 4d, and the linear‐fitting yields an activation energy of 13 meV. The fit indicates that the vertical transport through the CDG layers is governed by thermally activated transport26 and that this temperature dependence (although the junctions are fairly stable at each temperature, see Figure 4c inset) of the CDG film has an influence on the absolute junction resistance. At room temperature the resistance is dominated by the transport through the molecules but as the temperature is lowered the resistance of the CDG increases and can be expected to dominate at low temperatures.…”
mentioning
confidence: 94%